"the product of" ⇒ ___ * ___
86 ⇒ 86 . . . . . fills first blank
and
the depth of the river ⇒ d . . . . . fills second blank.
Your expression is
86 * d
Answer:
168
Step-by-step explanation:
0.28 * 600
Answer:
um try to type it out bc that made no sense
Step-by-step explanation:
Answer:
cross multiply
Step-by-step explanation:
<span>f(x)=(x^2 -2x)(3x-1) is a product and is most easily differentiated using the product rule:
f '(x) = (x^2 - 2x)(3) + (3x-1)(2x-2)
Now subst. 2 for x in this equation. We get:
f '(2) = (2^2 - 2(2))*3 + (3(2)-1)(2(2) -2), or
=3(4-4) + (6-1)(2) so f '(2) = 10 (answer)</span>